HIV Investment in Côte d’Ivoire : Optimized Allocation of HIV Resources for a Sustainable and Efficient HIV Response - World Bank (World Bank, Washington, DC, 2018)
This report summarizes the findings of an allocative efficiency analysis to support Côte d'Ivoire’s national HIV response. The study was conducted at the request of the Government of Côte d'Ivoire by the World Bank, the University of Bern, the Burnet Institute and the University of New South Wales in collaboration with UNAIDS. The analysis was conducted using Optima, a mathematical model of HIV transmission and disease progression that is population-based and flexible. Optima provides a formal method of optimization that quantitatively and objectively determines optimal allocations of HIV resources across numerous prevention and treatment programs to address multiple policy objectives. The model also estimates intervention impact, cost-effectiveness and return-on-investment, and provides analysis on the longer-term financial consequences of HIV infections and HIV investments.